Controlling the Right-Wing Political Parties: Informal Mechanisms of Co-optation and Marginalization in Serbia (2017–2024) - Jovanovic, Tamara (Political Life, 2025)
This article examines how right-wing parties in Serbia (2017–2024) are selectively included in or excluded from the political system through informal mechanisms of control. Drawing on theories of delegative democracy, informal institutions, competitive authoritarianism, and selective pluralism, it explores how the governing coalition co-opts, symbolically legitimizes, or conditionally tolerates opposition actors while limiting their substantive political impact. Through case studies of the Serbian Patriotic Alliance (SPAS), Zavetnici, Dveri, the New Democratic Party of Serbia (NDSS), the People’s Party (NS), the Serbian Radical Party (SRS), and Branimir Nestorović’s political movements, the article demonstrates that the right-wing opposition remains formally present, but its relevance depends on its contingent utility to those in power. The findings indicate that co-optation, selective visibility, and temporary marginalization are not anomalies but recurring governance patterns that sustain an illusory pluralism, while displacing genuine competition through personalized decision-making and media-driven control.